2014
DOI: 10.1002/jnm.1988
|View full text |Cite
|
Sign up to set email alerts
|

Gate leakage currents model for FinFETs implemented in Verilog‐A for electronic circuits design

Abstract: Because different conduction mechanisms can dominate the gate and drain/source leakage currents, mainly depending on the insulating materials used as gate dielectric, the dimensions of the gate structure, and the transistor operation regime, we proposed an improved analytical model to describe the behavior of these currents in silicon on insulator fin-shaped field-effect transistor devices by taking into account changes in the aforementioned factors. This model considers the direct tunneling, trap-assisted tun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…First, we observed that our gate leakage current model is verified as Rudenko [64], Garduno [32], Khan [65], and Golosov [66] have similar trends for IG: starting from a negative VG, IG first decreases significantly around 6-14 orders of magnitude, depending on the gate oxide, takes a minimum at some VG value, and then it increases steeply again.…”
Section: Leakage Current Performancesupporting
confidence: 64%
See 1 more Smart Citation
“…First, we observed that our gate leakage current model is verified as Rudenko [64], Garduno [32], Khan [65], and Golosov [66] have similar trends for IG: starting from a negative VG, IG first decreases significantly around 6-14 orders of magnitude, depending on the gate oxide, takes a minimum at some VG value, and then it increases steeply again.…”
Section: Leakage Current Performancesupporting
confidence: 64%
“…Nagy et al [ 31 ] explored nanowire FET architectures through a simulation in a VENDES finite element toolbox that integrated Schrödinger equation-based quantum corrected methods. Garduño [ 32 ] modeled gate leakage currents for many FinFET structures and the implementation was performed in Verilog-A.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in reference 25–29, a detailed analysis from the physical point of view was presented for the different components of gate tunneling currents observed in FinFETs. These tunneling currents include: (1) the direct tunneling current through the gate dielectric, along the channel, when the transistor is operating in inversion I G,inv ; (2) the tunneling current through the gate dielectric when the device is in depletion due to charges generated in the channel InormalG,gen$$ {I}_{\mathrm{G},\mathrm{gen}} $$; (3) the Trap Assisted Tunneling current in the drain overlap region I G,TAT ; (4) the gate‐induced drain leakage current (GIDL) through the overlap region at the drain when the device is in depletion, which is also called transversal GIDL or T‐GIDL, 29 InormalG,normalTGIDL$$ {I}_{\mathrm{G},\mathrm{T}-\mathrm{GIDL}} $$.…”
Section: Analytical Models For the Drain And Gate Currents Of Nanowir...mentioning
confidence: 99%